PERBANDINGAN HASIL BELAJAR BIOLOGI MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH DENGAN THE POWER OF TWO PADA KELAS XI MADRASAH ALIYAH MADANI ALAUDDIN PAO-PAO KABUPATEN GOWA - Herlina; Sri Mukminati Nur (Jurnal Biogenerasi, 2023)
This research is a type of quasi-experimental research, which aims to determine differences in cognitive, affective and psychomorphic learning outcomes of students by applying the Make a Match type cooperative learning model with The Power of Two in class XI students of Madrasah Aliyah Madani Alauddin Pao-pao, Gowa Regency. In this study, the experimental group I applied the Make a Match cooperative learning model and the experimental group II applied the The Power of Two cooperative learning model. The research instrument was a Learning Outcome Test (THB) to measure cognitive learning outcomes, and observation sheets to measure students' affective and psychomotor learning outcomes. Data were analyzed by descriptive and inferential statistics (Anacova and Anova with α = 0.05) with the help of the SPSS 18.0 for windows program. The results of this study indicate that there are significant differences in cognitive, affective and psychomorphic learning outcomes between students who are taught using the Make a Match type cooperative learning model and students who are taught using The Power of Two learning model.